CLINICO-LABORATORY CHARACTERISTICS OF HEPATITIS A IN PATIENTS WITH MARKERS OF HEPATITIS B VIRUS - E. V. Esaulenko; A. D. Bushmanova; A. A. Sukhoruk (Журнал инфектологии, 2017)
Aim: To characterize the modern trends of the hepatitis A clinic in adults with markers of the hepatitis B virus. Materials and methods: The study included 124 patients with hepatitis A, were hospitalized in Clinical Infectious Diseases Hospital named after S.P. Botkin in the period from 2012 to 2015. Diagnosis of hepatitis A and chronic hepatitis B was established on the basis of clinical and epidemiological criteria, confirmed by the results of a laboratory study. Two groups of patients were identified: 1 group – patients with hepatitis A as a monoinfection (n=85), 2 group – patients who had hepatitis A on a background of chronic hepatitis B (n=39). Results: An analysis of the age structure revealed that patients of the second group were older than the first. The analysis of gender structure established the same ratio of women and men (51,0% and 49,0%, respectively, p> 0,05) in the first group, in the second group the prevalence of women was found (64,0% and 36,0% respectively; p=0,001). General weakness, decreased appetite, and fever were more common for patients in the second group. Skin pruritus was more often in the first group. A comparative analysis of the two variants of hepatitis A showed that monoinfection of hepatitis A often occurs in mild form (47,0% and 18,0%, respectively, p=0,001). The severe form of the disease developed more often in patients of the second group (28,0% and 13,0%, respectively, p=0,02). Duration of hospitalization of patients and duration of icteric period was longer for hepatitis A on a background of chronic hepatitis B, regardless of the degree of severity. Conclusion: Modern hepatitis A in a third of cases is combined with chronic hepatitis B in people older than 40 years, and characterized by a higher frequency of severe icteric forms with severe cytolytic syndrome and requires a long hospitalization, which is accompanied by significant economic damage.